Experimental and numerical studies of high-chromium stainless steel welded I-section beam-columns - Sun, Yao (2022)
The present paper reports a comprehensive experimental and numerical investigation into the global stability of welded I-section beam-columns made of a newly developed grade EN 1.4420 high-chromium austenitic stainless steel. An experimental programme, adopting two high-chromium stainless steel welded I-sections, was firstly conducted and included initial geometric imperfections measurements and ten beam-column tests about the minor principal axis. The experimental programme was followed by a numerical modelling programme, where finite element models were developed and validated against the test results and then employed to perform parametric studies to generate further numerical data over a wide range of cross-section dimensions, member effective lengths and loading combinations. The obtained test and numerical results were adopted to evaluate the applicability of the codified design interaction curves for normal stainless steel welded I-section beam-columns, as set out in the European code and American design guide, to their new high-chromium counterparts. The evaluation results generally revealed that the Eurocode interaction curve leads to conservative failure load predictions, especially for high-chromium stainless steel Class 3 welded I-section beam-columns, owing mainly to the conservative bending end point (i.e. the cross-section minor-axis bending resistance) of the interaction curve, which is calculated without considering material strain hardening. The interaction curve specified in the American design guide was shown to result in an overall good level of design accuracy, but with many unsafe failure load predictions for high-chromium stainless steel compact welded I-section beam-columns, which can be principally attributed to the inadequate shape of the interaction curve. Finally, an improved interaction curve was proposed through employing the Eurocode interaction curve anchored to a more accurate bending end point, which is determined with rational exploitation of strain hardening by continuous strength method. The proposed interaction curve was shown to yield accurate, consistent and safe failure load predictions for high-chromium stainless steel welded I-section beam-columns.